A Noise Monitoring System Used for Substation Boundary: Part 1 – Devices and Synchronized Measurement Method. Issue 2 (June 2020) - Hou, Guoyan; Li, Shiping; Wang, Jian; Lan, Xinsheng; Tang, Ming; Zhou, Yiqian; Liu, Tao; Liu, Hongzhi
Abstract: Due to the interference of background noise, it is necessary to measure multi-point noise synchronously in the noise measurement of substation boundary. This measurement method not only increases the work intensity of measurement personnel, but also affects the reliability and accuracy of measurement data. In the long-term continuous noise monitoring task, there are still some problems, such as the data does not support online transmission, or cannot guarantee multi-point synchronous monitoring, or the standby time is insufficient. In order to solve the problem mentioned above, this paper provides a wide area synchronous noise measurement method and a continuous noise monitoring device. By deploying multiple sets of noise monitoring devices at the boundary of the substation and conducting wide area synchronous measurement, it can significantly improve the reliability of noise measurement data and improve the monitoring efficiency.